Moved by the past : discontinuity and historical mutation - Runia, Eelco (European perspectives: a series in social thought and cultural criticism., 2014)
Historians go to great lengths to avoid confronting discontinuity, searching for explanations as to why such events as the fall of the Berlin Wall, George W. Bush's invasion of Iraq, and the introduction of the euro logically develop from what came before. Moved by the Past radically breaks with this tradition of predating the past, incites us to fully acknowledge the discontinuous nature of discontinuities, and proposes to use the fact that history is propelled by unforeseeable leaps and bounds as a starting point for a truly evolutionary conception of history.